Ground-based ice-penetrating radar profiles collected on the Allan Hills blue ice region - Conway, Howard (IEDA: US Antarctic Program Data Center, 2017)
Low (7MHz) and high (20-100MHz) frequency ground-based ice-penetrating radar profiles collected on the Allan Hills blue ice region between January 19 and January 31, 2016. Data include .MAT files with low-frequency content; .DZX metadata, .DZT traces, and .KML tracklines with high-frequency content; and .PDF files with maps and figures.